THE SOCIAL DIMENSIONS OF VULGAR SPEECH USED BY BUGINESE AND AMERICAN SOCIETY - Rahmiati Rahmiati (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2019)
Vulgar speech is some phenomenon in social society, include Buginese and American society. This research aimed to analyze the social dimension of the vulgar language that used by the speakers of Buginese and English. The method used in this research is descriptive-qualitative method. The data were collected through library study and the field work. The result of this research shows the vulgar expressions were used in certain context, such as when people were angry or in a jokes situation. The vulgar language also used between them who have an intimate relationship. But nowadays, the phenomenon was changed. People used vulgar language not only between them who have intimate relationship but also uttered when they did know the person. Key words: Sociolinguistics, Vulgar Speech, Social Dimension